Pretreatment of vinegar residue and anaerobic sludge for enhanced hydrogen and methane production in the two-stage anaerobic system. (13th April 2015) - Wang, Zhenbin; Shao, Shuping; Zhang, Cunsheng; Lu, Daoli; Ma, Haile; Ren, Xiaofeng
Abstract: To enhance the conversion of vinegar residue to bio-energy gas, pretreatment of vinegar residue and anaerobic sludge were investigated in a two-stage anaerobic system. SEM and XRD were applied to observe the variation of cellulosic materials in vinegar residue. Alkaline and acid pretreatments were applied. The alkaline pretreatment of anaerobic sludge was an effective approach for hydrogenogen enrichment. Compared with oxalic acid, hydrochloric acid released more organic substrates. Analysis of SEM and XRD illustrated that the amorphous cellulosic structure of vinegar residue was significantly disintegrated by acid. The higher hydrogen yield, the shorter lag phase and digestion time indicated that the performance of anaerobic digestion was enhanced by pretreatment of vinegar residue and anaerobic sludge. The fracture of cellulosic materials and the higher concentration of reducing sugar explained the higher efficiency of the two-stage anaerobic digestion. Highlights: Anaerobic digestion of vinegar residue without pretreatment was hardly feasible. The alkaline pretreatment was an effective approach for hydrogenogen enrichment. The HCl released more organic substrates from vinegar residue than oxalic acid. The degradation of organic substrates explained the higher yield of bio-energy gas.